Estudo numérico do processo de extrusão de ABS considerando diferentes geometrias do bico extrusor e condições de operação - Barbosa, Gustavo Souza (2024)
The increasing popularity of additive manufacturing (AM) over the past decades is attributed to its lean production characteristics and the capacity to fabricate complex geometries. This growth has spurred industry efforts and investments in research to advance techniques that improve manufacturing quality, efficiency, and cost-effectiveness. This study aims to evaluate new investigative methods and approaches related to fused deposition modeling (FDM), commonly known as 3D printing, using ABS polymer as the material of choice. To assess the feasibility of extrusion simulation tools, two die geometries were considered: one with a 3 mm circular profile and another with a concave square profile inscribed within a 3 mm circle, based on the equipment available at the Mechanical Engineering Laboratory of UFSCar. For each die, combinations of temperature (80°C and 100°C) and ram speed (3 mm/s and 6 mm/s) were tested, yielding eight distinct conditions. These parameters were entered into the QformUK software to analyze its capabilities and limitations in simulating the polymer extrusion process. The results revealed that the Hensel-Spittel constitutive model is inadequate for accurately describing the rheological behavior of polymers, as the simulations did not replicate the experimentally observed geometries with precision. This shortfall is primarily attributed to the oversimplifications made when adapting constitutive models for metals to polymeric materials. Specifically, the Hensel-Spittel model proved insufficient in capturing the non-Newtonian behavior characteristic of polymers. Consequently, the simulations failed to account for advanced viscous effects, limiting the software’s ability to faithfully represent the polymer extrusion process. Future research should explore the use of more suitable tools, such as the development of specialized subroutines, to more accurately model polymer materials in QformUK.